Social representation of reproductive biotechnologies among nurses working in sexual and reproductive health - Ana Beatriz Azevedo Queiroz; Renata Porto dos Santos Mohamed; Elen Petean Parmejiani; Maria Aparecida Vasconcelos Moura; Ana Luiza de Oliveira Carvalho; Lidia Santos Soares (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to compare the social representations of reproductive biotechnologies among sexual and reproductive health nurses, and their links with professional practice. Methods: an analytical, comparative, qualitative research, supported by the Theory of Social Representation, carried out in May/2014-February/2015, with 32 nurses from the city of Rio de Janeiro. Semi-structured interview, analyzed by ALCESTE® software. Results: nurses not active in assisted human reproduction represent reproductive biotechnologies as unnatural methods of human reproduction, assessing the practice in this field as generalist and bureaucratic. Those who work represent as auxiliary and supporting nature for heterosexual couples, considering the innovative and specialized practice. Final considerations: each group presented specific contents and dimensions about reproductive biotechnologies. The representations are centered on moral, normative and ideological personal values, anchored in the traditional conceptions of human and family reproduction, but also collective, acquired in the professional routine, showing group identity and its distinct practices considering reproductive biotechnologies.